Ad gentes missions and new challenges - DOMASZK , ARKADIUSZ (Prawo Kanoniczne, 2019)
The Catholic Church is obliged to proclaim the Gospel of Jesus Christ. It is a missionary order directed to all people (ad gentes). Canon law perceives new situations: many migrations of people, including non-Christians, and the widespread influence of mass media, as new missionary challenges. The study aimed to investigate how Church law adapts to these new situations. The first chapter outlines what the ad gentes missions are. The next chapter presents the phenomenon of contemporary migration and the Church's response to this situation, especially to non-Christians in the European environment. Then the study outlined the situation of the so-called new media, their impact, and evangelization undertaken by the people of the Church in this area. In summary, it should be emphasized that awareness is the priority for the new challenges for ad gentes missions. Catholic missions do not take place only in distant countries, but through the presence of migrants and access to new means of communication, the missionary perspective has approached traditionally Christian countries. Every Catholic in the space of his daily life has the opportunity to be a missionary for his neighbours = migrants or co-users of the portal visited on the Internet. We need to think about the new solutions of the universal, particular or the smallest parish, so that the Christian message can reach every migrating person, including the Internet user. One should look for new ideas and their norms in the particular Church.